2013
DOI: 10.1002/ca.22191
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical basis of laparoscopic medial‐to‐lateral mobilization of the descending colon

Abstract: In laparoscopic colorectal resection, the medial-to-lateral approach has been largely adopted. This approach can be initiated by the division of either the inferior mesenteric artery (IMA) or the inferior mesenteric vein (IMV). This cadaveric study aimed to establish the feasibility of IMV dissection as the initial landmark of medial-to-lateral left colonic mobilization for evaluating the size of the peritoneal window between the IMV at the lower part of the pancreas and the origin of the IMA (IMA-IMV distance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…There is still some debate as to the expertise that is required to perform a laparoscopic LT, especially in the case of a fatty mesocolon [1]. Good anatomical knowledge of this area is mandatory to preserve the colic artery via the LT technique for tumors in the sigmoid colon and rectum [2,3,6]. During an LT procedure, the LCA may be damaged at its root during the dissection of the IMA.…”
Section: Introductionmentioning
confidence: 98%
“…There is still some debate as to the expertise that is required to perform a laparoscopic LT, especially in the case of a fatty mesocolon [1]. Good anatomical knowledge of this area is mandatory to preserve the colic artery via the LT technique for tumors in the sigmoid colon and rectum [2,3,6]. During an LT procedure, the LCA may be damaged at its root during the dissection of the IMA.…”
Section: Introductionmentioning
confidence: 98%
“…The anatomy of the IMA has been reported in previous studies and in anatomy textbooks. However, to our knowledge, the relationship between the IMA origin and the lower edge of the duodenum has only been reported in one study in recent decades ( 3 ). The authors measured IMA–D distance in 30 fresh cadavers and concluded that the IMA origin was located above the lower edge of the duodenum in 30% of cases, which is consistent with the results of the present study (27.69%).…”
Section: Discussionmentioning
confidence: 98%
“…253 lymph nodes, and the aorta is not routinely exposed to avoid autonomic nerve injury. However, the anatomical relationship between the root of the IMA and the duodenum is variable ( 3 ). In some patients, the IMA originates from the aorta above the lower edge of the duodenum, and the root of the IMA may not be adequately exposed without mobilising the third segment of the duodenum.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors choose between the first and the second approach based on the extent of the vascular window between the IMV and IMA. When the window is wide enough, they start from above; when it is less than 5 cm the dissection starts from the bottom instead [ 3 ]. However, this technique does not take into account any potential anatomical variation that may be responsible for errors in the identification of the IMA.…”
Section: Introductionmentioning
confidence: 99%